Case study: Effect of handrim diameter on performance in a Paralympic wheelchair athlete - Brizuela Costa, G.; Polo Rubio, M.; Llana Belloch, S.; Perez Soriano, P. (Adapted Physical Activity Quarterly, 2009)
This study, with a top T-52 class athlete, determines the relationship between stroke frequency (SF) and push time (PT) and wheelchair velocity (Wv) using different handrim diameters (HD) and the effect of different HDs on the athlete`s heart rate (HR) and blood lactate (LACT) at competition speeds. Wv shows a linear-direct relationship with SF but a linear-inverse relationship with PT (p < .001 in both cases). Using bigger handrims (0.37 m instead of 0.36 m), SF increases 6%, while PT decreases 27% (at 24 km/h). HR (p < .0001) increases with Wv and is also affected by HD with differences between the 0.34 m-0.36 m handrim group (lower values) and the 0.37 m handrim (higher values). Significant interaction (p < .0001) is identified between HD and Wv. LACT results seem to follow the same direction as HR. This methodology helped the athlete to choose the optimum HD, and his achievements (some world records) indicate that HD optimization could be highly profitable in sport terms.